PROBLEMATIKA DALAM PEMBELAJARAN MATEMATIKA PADA MASA PANDEMI COVID-19 KELAS V SDIT INSAN MULIA SURAKARTA - Kustiarini; Iffah Ananda (INSTRUKTUR, 2022)
The research was motivated by the presence of the Covid-19 pandemic, which had an impact on education. Researchers looked at the problems faced by mathematics teachers at SDIT Insan Mulia Surakarta during the Covid-19 pandemic. The objectives of the study were (1)to find out the problems faced. (2)the solutions taken by mathematics teachers during the Covid-19 pandemic. Descriptive qualitative research methodology collecting observational data, interviews, documentation. Data analiysis: data collection, data reduction, data presentation, drawing conclusions. The results of study show that there are several problems faced by research subjects teaching mathematics in VD class during the covid-19 pandemic, namely reduced lesson hours but a lot of material coverage, student conditioning; dealing with bad mood student, student do not really understand online material, facing students who are less enthusiastic about working on math problems, facing students who are independent in working on questions that are still lacking in literacy, especially he reading quality of students, the solutions taken by the teacher solves the problems, faced, namely before learning the research subject planning learning systematics, ice breaking, counting, motivation, guessing the correct answer is given a star reward, reviewing material learned online first, providing alternative ways sucs as donkey bridge in remembering, memorizing formulas, during limited PTM students are trained to do practice questions at school, give homework to read the material to be studied in the meeting